Análise Mensal [maio de 2012] - Pereima, João Basilio; Gomes, Antônio Luiz Costa; Nascimento, Ricardo; Conceição, Ronald (Revista Economia & Tecnologia, 2012)
Queda de juros: marketing ou realidade? Caminhando para o Pleno Emprego